Chemical Composition and Bioactivity of Essential Oils from Cymbopogon nardus L. and Rosmarinus officinalis L. Against Ulomoides dermestoides (Fairmaire, 1893) (Coleoptera: Tenebrionidae). Issue 3 (4th May 2021) - Caballero-Gallardo, Karina; Rodriguez-Niño, Dalila; Fuentes-Lopez, Katerin; Stashenko, Elena; Olivero-Verbel, Jesus
Abstract: Essential oils (EOs) represent valuable alternatives in handling pest insects in stored grains. The main objective of this study was to evaluate the chemical composition as well as the repellent, fumigant, and oviposition inhibition activities of the rosemary ( Rosmarinus officinalis ) and citronella ( Cymbopogon nardus ) EOs against Ulomoides dermestoides . Ethyl 3-[acetyl(butyl)amino] propanoate (IR3535), an active ingredient in repellent formulations was used as a positive control. The chemical compositions of the EOs were characterized by GC/MS. The EOs major compounds (>10 %) included 1, 8-cineole (24.6 %), α-pinene (17.7 %), camphor (12.4 %), and camphene (11.3 %) for rosemary, whereas for citronella, the most abundant components were citronellal (25.3 %), citronellol (17.9 %) and geraniol (11.6 %). The biological action observed was dependent on the concentration used. Both EOs showed 100 %-repellency at the highest tested concentration (16 μL/mL) with RC50 values lower than 2.6 μL/mL after 4 h-exposure. Contact toxicity results showed that all treatments had mortality rates lower than 40 %, while fumigant action did not exceed 25 %. The exposure of adult insects to sublethal concentrations of the two EOs significantly inhibited oviposition at 2 and 4 μL/mL. These data suggest that citronella and rosemary EOs, employing different toxicity mechanisms, could be useful candidates for formulations utilized in the management and pest control in stored products.